On The Stability of the Approximate Solution of the Galerkin Method for A Parabolic Boundary Problem with Divergent Main Part (Texas Journal of Engineering and Technology, 2022)
The article considers the application of the Galerkin method to the solution of boundary value problems of parabolic type with a divergent main part, when the boundary condition contains the time derivative of the desired function